Sobre la estabilidad asintótica de un problema parabólico de valor inicial (1993)
In this article we study the asymptotic stability of the solutions of an initial value semilinear problem of Dirichlet type. The linear part consists of an uniformly parabolic second order linear operator. The non-linearity is a T-periodic function on time, sufficiently regular. We consider the solutions of the associated periodic problem as the equilibrium state solutions.